CONTRIBUTION OF ROHANA KUDUS TO EMPOWERING MINANGKABAU WOMEN THROUGH VOICES AND WORKS - Ermagusti Ermagusti; Arrasyid Arrasyid; Rahmad Tri Hadi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This study aims to describe and analyze the contribution of Rohana Kudus in empowering Minangkabau women through her voice and work, both in the fields of religion, education, journalism, economics, social life, politics, and other fields. This study uses the gender deconstruction method, namely nurture. Called nurture because social and cultural factors create gender attributes and form stereotypes of a certain gender in society from generation to generation (culture). The results showed that due to the encouragement and demands to promote Minangkabau women, Rohana Kudus established the